Baseline integrity property measurement of legacy oil and gas wells for carbon storage projects. Issue 5 (9th May 2017) - Duguid, Andrew; Butsch, Robert; Carey, J. William; Celia, Michael; Chugunov, Nikita; Gasda, Sarah; Ramakrishnan, T. S.; Stamp, Vicki; Wang, James
Abstract: An import factor for long‐term storage is the integrity of wells penetrating the carbon storage reservoir. Well integrity will play a crucial role in establishing leakage risk in areas where there is a high density of existing (legacy) wells that could intersect operations including depleted petroleum fields where enhanced oil recovery or carbon storage will occur. The objective of this study was to develop methods that establish the baseline flow parameters from individual measurements in five wells in Wyoming. This paper describes the methods used to collect and analyze the data. The methods included isolation logging tools, in situ point and average permeability measurements, and laboratory tests on samples collected in the wells. The log results collected in the wells, considered in conjunction with the core measurements, indicate that interfaces and/or problems with cement placement related to eccentering provide preferential pathways for fluids, which increase the effective permeability of the barrier several orders of magnitude above that of intact cement. © 2017 Society of Chemical Industry and John Wiley & Sons, Ltd.